AN ANALYSIS OF INSTRUCTIONAL MEDIA USED BY THE ENGLISH TEACHER IN RELATION TO STUDENTS’ LEARNING INTEREST AND MOTIVATION IN SMP LABORATORIUM UNDIKSHA - ., Ida Bagus Made Ari Dwitya Senjaya; ., Drs.Gede Batan,MA; ., I Putu Ngurah Wage Myartawan, S.Pd., M.P (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bermaksud untuk menyelidiki jenis media pembelajaran yang digunakan oleh guru bahasa Inggris dalam kaitannya dengan minat dan motivasi siswa, dan masalah yang dihadapi oleh guru bahasa Inggris dalam menggunakan media pembelajaran. Penelitian ini menggunakan desain deskriptif kualitatif (Sandelowski, 2000) dan data dikumpulkan dengan observasi, kuesioner, dan wawancara untuk mendapatkan data. Hasil dari penelitian ini menunjukkan bahwa guru bahasa Inggris menggunakan enam jenis media pembelajaran, seperti (1) Slides power point, (2) Real Object, (3) Motion Picture (Video), (4) Menggambar, (5) Peta, dan (6) Internet. Penggunaan media pembelajaran memiliki hubungan dengan respon siswa pada minat dan motivasi belajar mereka. Hasilnya menunjukkan bahwa persentase minat siswa adalah positif (78, 5%) dan motivasi siswa positif (85, 6%) untuk belajar menggunakan media pembelajaran. Ada masalah umum yang dihadapi oleh guru bahasa Inggris dalam menggunakan media pembelajaran yaitu pemeliharaan alat yang digunakan untuk membantu guru bahasa Inggris untuk menunjukkan media pembelajaran.Kata Kunci : Media pembelaran, minat, motivasi. This study intends to investigate the types of instructional media used by the English teacher in relation to the students’ interest and motivation, and the problems encountered by the English teacher in using instructional media. This study used descriptive qualitative design (Sandelowski, 2000) and the data were collected from observations, a questionnaire, and an interview to obtain the data. The result of this study showed that the English teacher used six types of instructional media, such as (1) Slides of power point, (2) Real Object, (3) Motion Picture (Video), (4) Drawing, (5) Map, and (6) Internet. The used of instructional media had a relation to the students’ responses on their learning interest and motivation. The result showed that the percentage of the students’ interest was positive (78.5%) and the students’ motivation was positive (85.6%) to study using instructional media. There was a general problem encountered by the English teacher in using instructional media that is the maintenance of the tool that is used to help the English teacher to show the instructional media.keyword : Instructional media, interest, motivation.